Antioxidant and Antibacterial Assays on Polygonum minus Extracts: Different Extraction Methods. (30th March 2015) - Hassim, Norsyamimi; Markom, Masturah; Anuar, Nurina; Dewi, Kurnia Harlina; Baharum, Syarul Nataqain; Mohd Noor, Normah
Abstract : The effect of solvent type and extraction method was investigated to study the antioxidant and antibacterial activity of Polygonum minus . Two extraction methods were used: a solvent extraction using Soxhlet apparatus and supercritical fluid extraction (SFE). The antioxidant capacity was evaluated using the ferric reducing/antioxidant power (FRAP) assay and the free radical-scavenging capacity of 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assay. The highest polyphenol content was obtained from the medium polarity methanol extract of the leaf portion (645.60 ± 166.68 gallic acid equivalents/100 g (GAEs/100 g)). It also showed the highest antioxidant power for FRAP and DPPH radical inhibition and exhibited the largest inhibition zone in antibacterial activity on Bacillus subtilis (Gram+), Staphylococcus aureus (Gram+), and Escherichia coli (Gram−). The phase behavior and aldehyde profiles were further investigated using SFE with different cosolvents. The results indicated that a 50% ethanol-water cosolvent yielded the best aldehyde profiles in the presence of decanal, undecanal, and dodecanal.